Uso del mindfulness sobre indicadores de estrés en deportistas durante la etapa competitiva: Revisión sistemática - Holguín-Ramírez, Joaquín; Ramos Jimenez, Arnulfo; Gastélum-Cuadras, G; Cervantes-Borunda, Monica Sofía; Reyes-Acosta, Yesica; Hernández-Torres, Rosa Patricia (2020)
Mindfulness is a meditative practice that has proven to reduce psycho-physiological stress. Purpose: Analyze if mindfulness is effective to reduce psycho-physiological stress in athletes during their competitive season. Clinical studies that included different meditative techniques for stress reduction in athletes during the competitive phase was searched for in databases such as PubMed, Scopus and Web of Science (1985 to August 10, 2019), using the combinations of the words mindfulness, meditation, yoga, sport, athlete, intervention, stress, and cortisol. Only seven papers were located, three of them with a quantitative design, one as quantitative and three with mixed methodology. In the seven studies found (153 subjects; 134 men and 19 women) their authors mention that mindfulness was effective for reducing stress in athletes during the competitive season.